Quantification of environmental impacts for the Malaysian rubber industry using life cycle assessment / Zameri Mohamed - Zameri, Mohamed (2019)
Over the last 10 years, the Malaysian rubber industry’s contribution to Malaysia export earnings has increased significantly from RM 15.5 billion in 2003 to RM 33.7 billion in 2013. Due to its importance, the Malaysian Rubber Industry is included in the Malaysia National Key Economic Area as it is forecasted to contribute RM 52.9 billion in Malaysia Gross Nation Income by 2020. The main aim of this study is to provide a comprehensive inventory and detailed quantification of the environmental impact and greenhouse gases emission (GHGs) for the major part of the Malaysian rubber industry comprising the cultivation of rubber tree from cradle to grave and its three independents components (nursey, immature rubber and mature rubber), and standard Malaysian rubber (SMR) production from cradle to gate. The research methodologies used were questionnaire surveys with the objective to create a very comprehensive life cycle inventories tables representing the actual activities in the Malaysian rubber industry. The quantification of the environmental impact for this study was evaluated using Simapro software version 7.3.3 with Eco-indicator 99 as the default methodology while the quantification of GHGs emission was evaluated based on the global warming potential from the Intergovernmental Panel on Climate Change 2007 fourth assessment report using the same software. The results from the questionnaire survey indicate that the average annual consumption of ammonium sulphate and potassium chloride fertilizers in the cultivation of rubber trees from cradle to grave in Malaysia is estimated at 9.3% from total Malaysia consumption for 2014. The environmental impact from the average annual activities in the cultivation of rubber trees from cradle to grave in Malaysia represent 0.083% of the human health impact, 0.006% of the ecosystem quality impact and 0.111% of the resource depletion impact in Malaysia based on normalization procedure and these normalization results can be interpreted as representing 0.058% of the Malaysian environmental impact based on weighting procedure. The GHGs emission from the average annual activities in the cultivation of rubber trees from cradle to grave in Malaysia is 315.54 GgCO2eq and it represents 0.11% from the 2011 Malaysia GHGs emission. For the SMR production from cradle to gate, the environmental impact from the average annual production in Malaysia is 0.046% of the human health impact, 0.003% of the ecosystem quality impact and 0.176% of the resource depletion impact in Malaysia based on normalization procedure and can be summarized as representing 0.055% of the Malaysian environmental impact based on weighting procedure. The average annual GHGs emission from the production of SMR in Malaysia in this study is 229.41 GgCO2eq and it represent 72.7% from the average annual GHGs emission from the cultivation of rubber trees from cradle to grave in Malaysia for this study. The most significant aspect of this study is that this is the first LCA study ever carried out in Malaysia for the rubber industry.